Case reportComplete dissection of left anterior descending artery in a young woman after myocardial infarction - Özhan, Hakan; Bulur, Serkan; KayapInar, Osman; Türker, Yasin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Spontaneous coronary artery dissection (SCAD) is a rare clinical condition that causes acute coronary syndrome and sudden cardiac death. Herein, we report a case of left anterior descending artery dissection after myocardial infarction. On the third day of myocardial infarction after successful thrombolysis, the patient had recurrent chest pain without any ST wave elevation. She was referred to our clinic for coronary angiography which showed completely dissected left anterior descending (LAD) artery. She was referred to a tertiary centre with intravascular ultrasonography (IVUS) capability. Her control angiogram showed restored flow with only minimal dissection (so IVUS was not performed) in the mid LAD. The lesions in the distal and mid LAD were stented. The final angiogram showed TIMI-III flow. Percutaneous coronary intervention is the first choice of treatment in patients with single-vessel spontaneous coronary artery dissection with ongoing signs of ischemia.